Campylobacter jejuni and other emerging Campylobacteraceae in retail beef liver – an underestimated potential source?. (1st December 2022) - Lopez‐Cantillo, M.; Opazo‐Capurro, A.; Lopez‐Joven, C.; Vidal‐Veuthey, B.; Collado, L.
Abstract: Bovine by‐products, such as liver, could be an underestimated source of Campylobacter jejuni. Therefore, our aims were to evaluate the occurrence of C. jejuni and other Campylobacteraceae in retail beef liver and characterize their antibiotic resistance (ciprofloxacin, tetracycline, erythromycin and gentamicin) and potential genetic relationship by flagellin gene restriction fragment length polymorphism (flaA‐RFLP) and multilocus sequence typing with clinical strains. Seventy‐six out of 206 samples (36·9%) were positive for Campylobacter and related organisms. Arcobacter butzleri was the most frequently isolated species (21·8%), followed by C. jejuni (9·7%), C. fetus (7·8%) and C. coli (1%). The C. jejuni strains showed resistance to tetracycline (17·2%) or ciprofloxacin (6·9%), with only one strain resistant to both antibiotics. Meanwhile, 8·3% of ciprofloxacin resistance was observed in C. fetus. The other species showed no resistance. Most of the clonal complexes (CC) in which the C. jejuni genotypes were grouped (CC‐21, 42, 48 and 52), coincided with genotypes of clinical strains previously reported in Chile. As such, this study provides evidence that beef liver could be an underestimated route for resistant C. jejuni to humans. Further studies should assess whether this food could play a role in the transmission of other emerging Campylobacteraceae such as those reported here. Abstract: Significance and Impact of the Study: Campylobacteraceae has been associated with both intestinal and systemic disease in humans and animals; however, their transmission routes are not entirely clear. Although some species are transmitted by the consumption of chicken or beef meat, other foods such as beef liver have been far less studied. Therefore, this study provides information on retail bovine liver as an underestimated reservoir of diverse Campylobacteraceae, such as Arcobacter butzleri, Campylobacter fetus and Campylobacter coli and its antibiotic resistance profiles. Additionally, the genetic concordance found between Campylobacter jejuni isolates from livers with clinical strains isolated previously in Chile suggests a potential zoonotic relationship.